Empowering Local Communities: Promoting Financial Management in Village-Owned Enterprises (BUM Desa) for Sustainable Tourism Development - Hakiki, Moh. Saiful; Adinugroho, Mukhtar; Fajariansyah, Muhammad Dwi; Safiq, Moh. Nur (Indonesia Berdaya, 2023)
Local communities have increasingly become players that have significant roles in the tourism sector, utilizing their unique cultural and natural resources to attract visitors and stimulate local economic growth. Village-Owned Enterprises (BUM Desa) play a crucial role in driving sustainable tourism development by allowing local communities to actively participate in managing and benefiting from tourism activities. However, effective financial management within these enterprises remains a critical aspect that requires attention and improvement. This journal manuscript presents the outcomes of a community service activity conducted to address the financial management challenges faced by Village-Owned Enterprises in the tourism sector. The community service activities involved a series of workshop sessions aimed at providing practical guidance and insights to BUM Desa representatives. These sessions were supplemented by the publication of a book titled "Financial Management of Village-Owned Enterprises in the Sector of Tourism" and an article in the mass media platform Kumparan about the workshop activities. Through these efforts, local communities were equipped with the necessary tools and knowledge to make informed financial decisions, optimize revenue generation, and mitigate financial risks. By improving financial literacy, we can unlock the full potential of local tourism, leading to sustainable economic growth, social empowerment, and enhanced community well-being.